Metal-gallic acid amphiphilic ultra-small nano particle and preparation method thereof

By regulating the binding rate of metal ions and gallic acid in the aqueous solution system, metal-gallic acid amphiphilic ultra-small nanoparticles were successfully prepared, solving the problems of nanoparticle agglomeration and emulsification stability, and achieving excellent water dispersion and emulsification performance.

CN119613756AActive Publication Date: 2025-03-14JILIN UNIVERSITY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411961738.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-14
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

It is difficult to prepare amphiphilic ultra-small nanoparticles on a large scale, especially when maintaining the dispersion and emulsification stability of nanoparticles, there is a problem of particle agglomeration.

Method used

The aqueous solution system of low molecular weight polyvinylpyrrolidone (PVP) is used to regulate the binding rate of metal ions and gallic acid through the weak coordination interaction between N atoms and metal ions in PVP, and prepare metal-gallic acid amphiphilic ultra-small nanoparticles.

Benefits of technology

A method for preparing amphiphilic ultra-small nanoparticles under mild conditions is realized. The product has excellent water dispersion and emulsification properties, and is suitable for the preparation of a variety of metal-galactic acid amphiphilic nanoparticles, and is suitable for a wider pH range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613756A_ABST
    Figure CN119613756A_ABST
Patent Text Reader

Abstract

The invention discloses a metal-gallic acid amphiphilic ultra-small nano particle and a preparation method thereof, and belongs to the technical field of amphiphilic nano materials. Under all-water-system green preparation conditions, a water or tris buffer solution system of polyvinylpyrrolidone (PVP) with low molecular weight (M.W. = 6000-10000) is adopted, the binding speed between metal ions and gallic acid is slowed down by virtue of weak coordination interaction between N atoms in the PVP and the metal ions, the growth of the metal-gallic acid amphipathic ultra-small nanoparticles is inhibited, and the metal-gallic acid amphipathic ultra-small nanoparticles can be used for preparing the metal-gallic acid amphipathic ultra-small nanoparticles. And the metal-gallic acid amphipathic ultra-small nano particles are prepared. The method is mild in reaction condition, simple to operate, green and environment-friendly, good in product dispersity and convenient for large-scale mass production, and has good applicability to preparation of various metal-gallic acid amphiphilic ultra-small nanoparticles, the prepared product has excellent water dispersion performance and good emulsifying capacity, and the HLB (hydrophile-lipophile balance) value of the product is 12-14.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of amphiphilic nanomaterials, and specifically relates to metal-gallic acid amphiphilic ultrasmall nanoparticles and a preparation method thereof. Background Art

[0002] Solid nanoparticles of a certain size and desired wettability have been shown to be alternatives to traditional emulsifiers. For example, hydroxyapatite, nanosilica, molecular sieves, carbon materials, clays, etc. have been modified and used in the preparation of Pickering emulsions. Pickering emulsions use solid particles instead of traditional polymer surfactants to form more stable emulsions that can obtain many useful properties. In addition, when solid particles are relatively safe in the body, they are more biocompatible. By selectively modifying the surface of nanoparticles to achieve targeted modification of materials to meet the requirements of the target use environment, it can be widely used in biomedicine, biomedicine, food, fine chemical synthesis, cosmetics and other fields.

[0003] Gallic acid is a polyphenolic compound with natural antioxidant activity. Since it contains five oxygen atoms on both sides of the molecule and the distance between the phenolic oxygen atoms is large, gallic acid can form a stable complex with transition metal ions, thus having strong reducing and coordination properties. Gallic acid derivatives are widely used in the fields of medicine, food, cosmetics, etc. The relevant soluble salts of iron, cobalt, nickel, and copper ions are low in price and easily available, and can be used as the coordination center ions to form stable amphiphilic (both hydrophilic and lipophilic) nanoparticles with gallic acid.

[0004] In the emulsification application field of amphiphilic nanoparticles, nanoparticles with smaller particle sizes are often more likely to form a dense emulsion system with small emulsion droplets and maintain the stability advantage of Pickering emulsion. However, affected by the specific surface energy, after the solid is obtained by drying from the preparation system, the redispersion of ultrasmall nanoparticles is usually troubled by agglomeration. The lack of large-scale preparation methods for amphiphilic ultrasmall nanoparticles limits their development and application. Metal ions and gallic acid can quickly coordinate and stably form ultrasmall nanoparticles under certain conditions, and some studies have been applied to the biomedical field. However, the research on the amphiphilic properties (hydrophilic and lipophilic) of "metal-gallic acid" ultrasmall nanoparticles has not been taken seriously. Therefore, it is very important to study a preparation method for amphiphilic ultrasmall nanoparticles based on "metal-gallic acid" complexes. Summary of the invention

[0005] The invention aims to provide a metal-gallic acid amphiphilic ultra-small nanoparticle and a preparation method thereof. The metal element is Fe, Co, Ni or Cu.

[0006] The invention adopts a low molecular weight (MW=6000-10000) polyvinyl pyrrolidone (PVP) aqueous solution system under the green preparation condition of the whole water system, relies on the weak coordination interaction between the N atom in the PVP and the metal ion, slows down the binding speed between the metal ion and gallic acid, inhibits the growth of metal-gallic acid amphiphilic ultra-small nanoparticles, and prepares metal-gallic acid amphiphilic ultra-small nanoparticles. For cobalt and nickel metal ions with poor nucleation ability with gallic acid, we adopt a method of regulating the pH value of a tris buffer solution to controllably promote the growth speed of the nanoparticles.

[0007] The preparation method of the metal-gallic acid amphiphilic ultra-small nanoparticles provided by the present invention has mild reaction conditions, simple operation, green environmental protection (no organic solvent is used), good product dispersibility, and is convenient for large-scale mass production. It has good applicability for the preparation of various metal-gallic acid amphiphilic ultra-small nanoparticles, and the prepared products have excellent water dispersibility. It is used for the emulsification of toluene / water and n-octane / water two-phase systems, showing excellent emulsification performance, and showing good emulsification ability under wide pH solution conditions. In addition, the prepared metal-gallic acid amphiphilic ultra-small nanoparticles, as a partially hydrophilic solid emulsifier material, have an HLB value between 12 and 14.

[0008] The method for preparing the metal-gallic acid amphiphilic ultra-small nanoparticles of the present invention comprises the following steps:

[0009] (1) dissolving ferric chloride hexahydrate, cobalt chloride, nickel chloride hexahydrate or cupric chloride dihydrate in water to prepare a metal ion aqueous solution;

[0010] (2) adding the metal ion aqueous solution obtained in step (1) to a tris buffer solution system of low molecular weight polyvinyl pyrrolidone or a polyvinyl pyrrolidone aqueous solution system, stirring and dispersing to promote the weak coordination reaction between polyvinyl pyrrolidone and the metal ion;

[0011] (3) slowly adding the gallic acid aqueous solution to the solution obtained in step (2), and continuously stirring the reaction at a certain temperature for a period of time;

[0012] (4) Transfer the reaction system obtained in step (3) into a dialysis bag (20000Da), replace the water every 10 to 15 hours, and continue dialysis for 2 to 3 days;

[0013] (5) heating and drying the contents of the bag after dialysis in step (4) at 90-110° C. to obtain the metal-gallic acid amphiphilic ultrasmall nanoparticles.

[0014] Dispersing the metal-gallic acid amphiphilic ultrasmall nanoparticles (Fe-GA, Co-GA, Ni-GA, Cu-GA) obtained in step (5) in water to prepare a nanoparticle dispersion with a concentration of 2 to 10 mg / mL, and measuring the surface tension using a surface tension meter;

[0015] The metal-gallic acid amphiphilic ultrasmall nanoparticles (Fe-GA, Co-GA, Ni-GA, Cu-GA) obtained in step (5) are dispersed in water to prepare a nanoparticle dispersion with a concentration of 1 to 3 mg / mL, the dispersion is mixed with toluene, cyclohexane, and n-octane (volume ratio of 1:1), and ultrasonically emulsified at a certain power (180 W to 360 W) for a certain time (1 to 3 min), and the emulsification rate is determined after standing for 24 hours, and the microscopic state of the emulsified bubbles is studied using an optical microscope;

[0016] The metal-gallic acid amphiphilic ultra-small nanoparticles (Fe-GA, Co-GA, Ni-GA, Cu-GA) obtained in step (5) are dispersed in a water system (pH = 1 to 13) whose pH is regulated by HCl or NaOH to prepare metal-gallic acid aqueous dispersions and polyvinyl pyrrolidone aqueous dispersions with a concentration of 1 to 3 mg / mL at different pH values. The product dispersions and polyvinyl pyrrolidone aqueous dispersions at different pH values ​​are mixed with n-octane in a volume ratio of 1:1, and ultrasonicated for a certain time (1 to 3 minutes) at a certain power (180W to 360W) under a probe ultrasonic instrument. After standing for 24 hours, the emulsification rate is determined, and the microscopic state of the emulsified bubbles is detected by a microscope.

[0017] Preferably, in the metal ion aqueous solution of step (1), the concentration of metal ions is 0.3 to 0.5 mol / L;

[0018] Preferably, in step (2), the tris buffer solution system of low molecular weight polyvinyl pyrrolidone is prepared by adding low molecular weight polyvinyl pyrrolidone to a tris buffer solution with a pH of 7.3 to 7.5; the aqueous solution system of low molecular weight polyvinyl pyrrolidone is prepared by adding low molecular weight polyvinyl pyrrolidone to deionized water; the concentration of polyvinyl pyrrolidone is 6000 to 9000 ppm, and the molecular weight of polyvinyl pyrrolidone is MW = 6000 to 10000;

[0019] Preferably, in step (2), after the metal ion aqueous solution is added to the tris buffer solution system of low molecular weight polyvinyl pyrrolidone or the aqueous solution system of low molecular weight polyvinyl pyrrolidone, the concentration of the metal ion is 6.67 to 11.1 mmol / L;

[0020] Preferably, the reaction temperature in step (3) is 20-30° C., the reaction time is 2-12 h, and the molar ratio of gallic acid to metal ions is 0.6-0.9:1.

[0021] According to an embodiment of the present invention, compared with traditional emulsifiers, it can be applied to a wider pH range, and the toluene / water and n-octane / water emulsion systems prepared by using ultra-small metal-gallic acid amphiphilic nanoparticles have better stability. In addition, from the results of surface tension measurement, the prepared metal-gallic acid product exhibits excellent surface activity, which can significantly reduce the surface tension of the water system. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 A transmission electron microscope (TEM) image of the Fe-GA amphiphilic ultrasmall nanoparticles prepared in Example 1;

[0023] Figure 2 The dynamic light scattering particle size distribution diagram of the ultra-small nanoparticles prepared in the embodiment; wherein, Figure 2 a) is a dynamic light scattering particle size distribution diagram of Fe-GA ultrasmall nanoparticles prepared in Example 1; Figure 2 b) is a dynamic light scattering particle size distribution diagram of the Co-GA ultrasmall nanoparticles prepared in Example 2; Figure 2 c) is a dynamic light scattering particle size distribution diagram of Ni-GA ultrasmall nanoparticles prepared in Example 3; Figure 2 d) is a dynamic light scattering particle size distribution diagram of the Cu-GA ultrasmall nanoparticles prepared in Example 4;

[0024] Figure 3 The microscopic morphology of the emulsion droplets of the Fe-GA, Co-GA, Ni-GA, and Cu-GA amphiphilic ultrasmall nanoparticles prepared in Examples 1 to 4 in toluene / water, cyclohexane / water, and n-octane / water two-phase emulsion systems;

[0025] Figure 4 Emulsification rate of Fe-GA, Co-GA, Ni-GA, Cu-GA amphiphilic ultra-small nanoparticles prepared in Examples 1 to 4 in toluene / water, cyclohexane / water, n-octane / water two-phase emulsion systems and average emulsion particle size distribution diagram;

[0026] Figure 5 Appearance photos of n-octane / water two-phase emulsion systems of Fe-GA, Co-GA, Ni-GA, Cu-GA amphiphilic ultrasmall nanoparticles and polyvinyl pyrrolidone at different pH values ​​prepared in Examples 1 to 4;

[0027] Figure 6The emulsification rate of the n-octane / water two-phase emulsion system of Fe-GA, Co-GA, Ni-GA, Cu-GA amphiphilic ultra-small nanoparticles and polyvinyl pyrrolidone prepared in Examples 1 to 4 at different pH values ​​and the statistical distribution diagram of the average particle size of the emulsion droplets;

[0028] Figure 7 This is a graph showing the change in average particle size of emulsion droplets of the Fe-GA, Co-GA, Ni-GA, and Cu-GA amphiphilic ultrasmall nanoparticles prepared in Examples 1 to 4 in an oil-water system with a gradient HLB value. DETAILED DESCRIPTION

[0029] In order to explain the technical points and application scenarios of the present invention in more detail, so as to facilitate professionals in the field to manufacture and use the technical content of the present invention, a more detailed and complete description will be given below in combination with the accompanying drawings and specific embodiments. It should be noted that the embodiments described below are not all embodiments, but only embodiments of the preferred invention conditions of this patent. The required drugs and instruments involved in the present invention can all be purchased through normal commercial channels.

[0030] Example 1

[0031] Add 330 mg of polyvinyl pyrrolidone (MW8000) to 44 mL of deionized water, stir and dissolve at room temperature to obtain a polyvinyl pyrrolidone aqueous solution system with a concentration of 7500 ppm; add 1 mL of ferric chloride hexahydrate (0.37 mol / L) solution, stir and disperse for 30 minutes to ensure that polyvinyl pyrrolidone regulates the growth of nanoparticles in the subsequent nanoparticle formation process. 5 mL and 10 mg / mL of gallic acid aqueous solution were slowly added to the system, and the system quickly turned black. After stirring the reaction at room temperature for 10 hours, the system was transferred to a dialysis bag (20000 Da) for dialysis, and the water was changed every 12 hours. Dialysis was continued for 2 days to remove free chloride ions, polyvinyl pyrrolidone and other impurities. The microscopic morphology was photographed using a transmission electron microscope, and the results are as follows: Figure 1 As shown in the figure, the Fe-GA amphiphilic ultra-small nanoparticles are microscopically uniformly spherical. Dynamic light scattering (DLS) was used to measure the particle size distribution of Fe-GA ultra-small nanoparticles. Figure 2 As shown in a, its average diameter is 5.46nm. Finally, the bag liquid after dialysis was dried at 100°C to obtain 224mg of black Fe-GA ultra-small nanoparticles. The iron content in Fe-GA was 1.59wt%. The surface tension of the 2mg / mL aqueous dispersion prepared by dispersing the product was 8.07% lower than that of pure water.

[0032] Example 2

[0033] 330 mg of polyvinyl pyrrolidone (MW8000) was added to 44 mL of tris buffer solution with a pH of 7.4, and stirred at room temperature to dissolve to obtain a polyvinyl pyrrolidone tris buffer solution system with a concentration of 7500 ppm; 1 mL of cobalt chloride (0.37 mol / L) solution was added thereto, and stirred and dispersed for 30 minutes to ensure that polyvinyl pyrrolidone regulates the growth of nanoparticles in the subsequent nanoparticle formation process. 5 mL of a 10 mg / mL aqueous solution of gallic acid was slowly added dropwise to the system, and the system quickly turned brown-yellow. After stirring the reaction at room temperature for 10 hours, the system was transferred to a dialysis bag (20000 Da) for dialysis, and the water was changed every 12 hours for 2 consecutive days to remove impurities such as free chloride ions and polyvinyl pyrrolidone. Dynamic light scattering (DLS) was used to measure the particle size distribution of Co-GA ultrasmall nanoparticles. Figure 2 As shown in Fig. b, its average diameter is 10.20 nm. Finally, the bag solution after dialysis was dried at 100°C to obtain 265 mg of brown-black Co-GA ultra-small nanoparticles. The cobalt content in Co-GA was 1.21 wt%. The surface tension of the 2 mg / mL aqueous dispersion prepared by dispersing the product was 8.38% lower than that of pure water.

[0034] Example 3

[0035] Add 330 mg of polyvinyl pyrrolidone (MW8000) to 44 mL of tris buffer solution with a pH of 7.4, stir and dissolve at room temperature to obtain a polyvinyl pyrrolidone tris buffer solution system with a concentration of 7500 ppm; add 1 mL of nickel chloride hexahydrate (0.37 mol / L) solution, stir and disperse for 30 minutes to ensure that polyvinyl pyrrolidone regulates the growth of nanoparticles in the subsequent nanoparticle formation process. Slowly add 5 mL of a 10 mg / mL gallic acid aqueous solution to the system, and the system quickly turns brown-yellow. After stirring the reaction at room temperature for 10 hours, transfer the system to a dialysis bag (20000 Da) for dialysis, change the water every 12 hours, and dialyze continuously for 2 days to remove impurities such as free chloride ions and polyvinyl pyrrolidone. Dynamic light scattering (DLS) was used to measure the particle size distribution of Ni-GA ultrasmall nanoparticles. Figure 2 c, the average diameter is 9.18nm. Finally, the bag solution after dialysis was dried at 100°C to obtain 263mg brown-black Ni-GA ultra-small nanoparticles, the nickel content in Ni-GA was 0.86wt%, and the surface tension of the 2mg / mL aqueous dispersion prepared by dispersing the product was 7.37% lower than that of pure water.

[0036] Example 4

[0037] Add 330 mg of polyvinyl pyrrolidone (MW8000) to 44 mL of deionized water, stir and dissolve at room temperature to obtain a polyvinyl pyrrolidone aqueous solution system with a concentration of 7500 ppm; add 1 mL of cupric chloride dihydrate (0.37 mol / L) solution, stir and disperse for 30 minutes to ensure that polyvinyl pyrrolidone regulates the growth of nanoparticles in the subsequent nanoparticle formation process. 5 mL and 10 mg / mL of gallic acid aqueous solution were slowly added to the system, and the system quickly turned brown. After stirring the reaction at room temperature for 10 hours, the system was transferred to a dialysis bag (20000 Da) for dialysis, and the water was changed every 12 hours. Dialysis was continued for 2 days to remove free chloride ions, polyvinyl pyrrolidone and other impurities. Dynamic light scattering (dls) was used to measure the particle size distribution of Cu-GA ultrasmall nanoparticles. Figure 2 d, the average diameter is 7.23nm. Finally, the bag solution after dialysis was dried at 100℃ to obtain 230mg brown-black Cu-GA ultra-small nanoparticles. The copper content in Cu-GA was 0.68wt%. The surface tension of the 2mg / mL aqueous dispersion prepared by dispersing the product was 6.68% lower than that of pure water.

[0038] Table 1 shows the surface tension of the aqueous dispersion of metal-gallic acid amphiphilic ultra-small nanoparticles (Fe, Co, Ni, Cu) prepared in Examples 1-4 at 25°C

[0039]

[0040]

[0041] Example 5

[0042] The metal-gallic acid amphiphilic ultrasmall nanoparticles prepared in Examples 1, 2, 3, and 4 were used as raw materials to prepare 2 mg / mL aqueous dispersions, and then the dispersions were mixed with toluene, cyclohexane, and n-octane at a water-to-oil volume ratio of 1:1, and then ultrasonically emulsified for 3 minutes (instrument: SCIENTZ-1500F ultrasonic disperser of Ningbo Xinzhi Biotechnology Co., Ltd.; parameters: 3Min, 30%, 2.0Sed, ultrasonic power of 270W), and the emulsification rate was measured after standing for 24 hours, and the microscopic state of the emulsified bubbles was studied with an optical microscope. The state of the emulsion droplets under the microscope is as follows: Figure 3 As shown, the emulsion droplets are dense and the droplet size distribution is relatively uniform. Figure 4The results show that metal-gallic acid (Fe, Co, Ni, Cu, PVP) can be used as surfactants to emulsify three organic solvents to obtain the emulsification rate and average emulsion droplet size. The results show that metal-gallic acid ultra-small nanoparticles have better emulsification performance than polyvinyl pyrrolidone (8000 M.W.). Specifically, in the toluene / water system, although the emulsification rates of PVP (8000M.W.) and metal-gallic acid (Fe, Co, Ni, Cu) are both around 75%, the emulsion droplet size of the latter is only 50% to 60% of that of the former; in the cyclohexane / water and n-octane / water systems, after standing for one day, the emulsion system of PVP (8000M.W.) has completely broken, while the metal-gallic acid can still maintain an emulsification rate of 70% to 75% and a dense emulsion state with an average droplet size of 20μm, indicating that the metal-gallic acid amphiphilic ultrasmall nanoparticle emulsifier has better emulsification properties and the stability of the prepared emulsion is significantly better than (PVP, 8000M.W.).

[0043] Example 6

[0044] The ultrasmall metal-gallic acid amphiphilic ultrasmall nanoparticles and polyvinyl pyrrolidone (8000 MW) prepared in Examples 1, 2, 3, and 4 were respectively dispersed in a water system with a certain pH value (pH = 1, 3, 5, 7, 9, 11, and 13) regulated by NaOH or HCl to prepare metal-gallic acid aqueous dispersions and polyvinyl pyrrolidone aqueous dispersions with a concentration of 2 mg / mL at different pH values. The metal-gallic acid aqueous dispersion and the polyvinyl pyrrolidone aqueous dispersion were then mixed with n-octane in an oil-water volume ratio of 1:1, and ultrasonicated for 3 min at a power of 270 W using a probe ultrasonic instrument. The emulsification rate was determined after standing for 24 h, and the average particle size of the emulsion droplets was observed and counted using a microscope. Figure 5 The emulsification conditions of ultrasmall metal-gallic acid amphiphilic ultrasmall nanoparticles (Fe, Co, Ni, Cu) and polyvinylpyrrolidone (PVP, 8000 M.W.) under different pH conditions are given. Figure 6 The emulsification rate of ultra-small metal-gallic acid amphiphilic ultra-small nanoparticles and polyvinylpyrrolidone (PVP, 8000M.W.) at different pH values ​​and the average particle size of the emulsion droplets are given. Figure 5 and Figure 6As a result, we can conclude that metal-gallic acid amphiphilic ultra-small nanoparticles have a wider pH range of application as solid emulsifiers, among which Fe-GA, Co-GA, Ni-GA can still show excellent surface activity in aqueous solution in the pH range of 1 to 13, and Cu-GA can show good emulsification performance in the oil-water two-phase system. Compared with traditional polyvinyl pyrrolidone nonionic surfactants, it shows a wider range of application.

[0045] Example 7

[0046] Table 2 is the ratio data of the mixed oil phase of cottonseed oil and turpentine oil with gradient HLB value

[0047]

[0048] The metal-gallic acid ultra-small amphiphilic nanoparticles prepared in Examples 1, 2, 3, and 4 were dispersed in water to prepare a 1 mg / mL aqueous dispersion. According to the operation method of the traditional emulsification method, a mixed oil phase with a gradient HLB value was prepared with cottonseed oil and turpentine oil according to the ratio in Table 2. 4 mL of the 1 mg / mL nanoparticle dispersion was added to the configured gradient oil phase with HLB values ​​of 11, 12, 13, 14, and 15, and ultrasonicated at 270 W for 2 minutes, and allowed to stand for 1 week, and the average particle size of the emulsified bubbles was detected and counted. Figure 7 The particle size of the emulsion droplets in the oil-water system with a gradient HLB value is shown. We can believe that the prepared metal-gallic acid amphiphilic ultrasmall nanoparticles are a surfactant with an HLB value in the range of 12 to 14, which is hydrophilic.

Claims

1. A method for preparing metal-gallic acid amphiphilic ultra-small nanoparticles, the steps of which are as follows: (1) dissolving ferric chloride hexahydrate, cobalt chloride, nickel chloride hexahydrate or cupric chloride dihydrate in water to prepare a metal ion aqueous solution; (2) adding the metal ion aqueous solution obtained in step (1) to a tris buffer solution system of low molecular weight polyvinyl pyrrolidone or a polyvinyl pyrrolidone aqueous solution system, stirring and dispersing to promote the weak coordination reaction between polyvinyl pyrrolidone and the metal ion; (3) slowly adding the gallic acid aqueous solution to the solution obtained in step (2), and continuously stirring the reaction at a certain temperature for a period of time; (4) Transfer the reaction system obtained in step (3) into a 20,000 Da dialysis bag, replace the water every 10 to 15 hours, and continue dialysis for 2 to 3 days; (5) heating and drying the contents of the bag after dialysis in step (4) at 90-110° C. to obtain the metal-gallic acid amphiphilic ultrasmall nanoparticles.

2. The method for preparing a metal-gallic acid amphiphilic ultra-small nanoparticle according to claim 1, characterized in that: In the metal ion aqueous solution of step (1), the concentration of metal ions is 0.3-0.5 mol / L.

3. The method for preparing a metal-gallic acid amphiphilic ultra-small nanoparticle according to claim 1, characterized in that: In step (2), the tris buffer solution system of low molecular weight polyvinyl pyrrolidone is prepared by adding low molecular weight polyvinyl pyrrolidone into a tris buffer solution with a pH value of 7.3 to 7.5; the aqueous solution system of low molecular weight polyvinyl pyrrolidone is prepared by adding low molecular weight polyvinyl pyrrolidone into deionized water; the concentration of polyvinyl pyrrolidone is 6000 to 9000 ppm, and the molecular weight of polyvinyl pyrrolidone is MW=6000 to 10000.

4. The method for preparing a metal-gallic acid amphiphilic ultra-small nanoparticle according to claim 1, characterized in that: In step (2), after the metal ion aqueous solution is added to the tris buffer solution system of low molecular weight polyvinyl pyrrolidone or the aqueous solution system of low molecular weight polyvinyl pyrrolidone, the concentration of the metal ions is 6.67 to 11.1 mmol / L.

5. The method for preparing a metal-gallic acid amphiphilic ultra-small nanoparticle according to claim 1, characterized in that: In step (3), the reaction temperature is 20-30° C., the reaction time is 2 h-12 h, and the molar ratio of gallic acid to metal ions is 0.6-0.9:

1.

6. A metal-gallic acid amphiphilic ultra-small nanoparticle, characterized in that: The method is prepared by any one of claims 1 to 5.

Citation Information

Patent Citations

  • Method for chemically regulating and controlling dispersion degree and particle diameter of nanometer ferroferric oxide on basis of gallic acid-metal ion coordination

    CN107522239A

  • Preparation method of Fe-GA hollow metal organic framework material

    CN113444256A

  • Needle-shaped copper-gallic acid nano enzyme as well as preparation method and application thereof

    CN116077527A

  • Iron gallate nano network as well as preparation method and application thereof

    CN118370726A

  • Near infra-red light responsive gold decorated solid lipid nanoparticles and process for preparation thereof

    IN202121006011A